Ileal gastrointestinal stromal tumor causing mesenteric gangrene. Issue 4 (20th April 2022) - Beji, Hazem; Bouassida, Mahdi; Zribi, Slim; Touinsi, Hassen
Abstract: To our knowledge, this is one of the rare literature reports of an ileal GIST complicated with mesenteric gangrene. We reported successful surgical treatment. Infection of GIST is an extremely rare complication that should be treated with no delays to avoid rupture and peritonitis. Abstract : Ileal gastrointestinal stromal tumors are rare. Mesenteric gangrene is an extreme rare complication. Diagnosis is difficult. Surgical treatment should not be delayed.